Biphasic Neuroprotective and Pro-Inflammatory Synergistic Effects of Red Laser Photobiomodulation Combined with Levodopa in a Rotenone-Induced SH-SY5Y Cell Model of Parkinson's Disease: An in Vitro Study - Abbas, Ghasaq Mohammed; Selman Mohammed Selman; Kaiser N. Madlum (International Journal of Medical Toxicology and Forensic Medicine, 2026)
Background: Parkinson's disease is a progressive neurodegenerative disorder with no curative therapy. Red laser photobiomodulation (PBM) has emerged as a potential neuroprotective strategy because of its antioxidant and mitochondrial biostimulatory properties. To evaluate the neuroprotective efficacy of individual and combined levodopa and red laser PBM pre-treatment against rotenone-induced neurotoxicity in SH-SY5Y neuroblastoma cells. Methods: SH-SY5Y cells were pre-treated with levodopa (25, 50, 100 µM), continuous-wave red laser PBM (630–660 nm, 100 mW, 0.5 W/cm²; 10, 20, 40 s), or their combined configurations for 2 h, followed by a 24-hour rotenone (50 µM) challenge. Cell viability (MTT), IL-1β (ELISA), MDA (TBARS), and total antioxidant capacity (TAOC) were quantified. Results: Rotenone induced cytotoxicity, elevated IL-1β and MDA levels, and depleted TAOC. Individual Levodopa (50 µM) reduced MDA (P < 0.0001) and restored TAOC (P < 0.0001) but failed to rescue viability (P > 0.05). A 20-second red laser exposure (2 J, 10 J/cm²) optimally enhanced cell survival (P = 0.0087), reduced lipid peroxidation (P = 0.0002), and recovered TAOC (P = 0.0004), demonstrating a biphasic dose-response. Specific combined regimens (Triple Pre 1 and 2) triggered a synergistic surge in IL-1β (P < 0.0001), driven by hypermetabolic cross-talk between levodopa auto-oxidation and PBM biostimulation, whereas Triple Pre 3 maintained cytokine homeostasis (P > 0.05 vs. rotenone control). Conclusion: Red laser PBM provides biphasic, dose-dependent neuroprotection by restoring bioenergetics and antioxidant defenses; however, its combination with levodopa can provoke severe pro-inflammatory synergy, necessitating strict dosimetric thresholding in multimodal Parkinson's interventions.